2014
DOI: 10.5535/arm.2014.38.5.637
|View full text |Cite
|
Sign up to set email alerts
|

Post-Polio Syndrome and Risk Factors in Korean Polio Survivors: A Baseline Survey by Telephone Interview

Abstract: ObjectiveTo obtain information on the socioeconomic, medical, and functional status of polio survivors, and to use these results as the preliminary data for establishing the middle-aged cohort of polio survivors.MethodsThe subjects were recruited based on the medical records of multiple hospitals and centers. They were assessed through a structured questionnaire over the phone. Post-poliomyelitis syndrome (PPS) was identified according to the specified diagnostic criteria. Differences between polio survivors w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
1
4

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 32 publications
1
11
1
4
Order By: Relevance
“…Similarly, Talebian et al reported 55.66% prevalence for PPS syndrome [8]. In a study on the prevalence of PPS syndrome and its risk factors, Bang et al reported that on average 61.6% of the people with a history of polio show the symptoms of PPS and most of them are middle-aged [7]. Ramlow et al also reported a PPS prevalence of 28.5% [14].…”
Section: Discussionmentioning
confidence: 97%
See 4 more Smart Citations
“…Similarly, Talebian et al reported 55.66% prevalence for PPS syndrome [8]. In a study on the prevalence of PPS syndrome and its risk factors, Bang et al reported that on average 61.6% of the people with a history of polio show the symptoms of PPS and most of them are middle-aged [7]. Ramlow et al also reported a PPS prevalence of 28.5% [14].…”
Section: Discussionmentioning
confidence: 97%
“…Body weight-bearing muscles such as leg muscles are involved in this disease more than the other muscles [7]. Generally, PPS is not a life-treating syndrome [1,7].…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations